019 Differentiating status epilepticus from prolonged psychogenic non-epileptic seizures – can peripheral cell ratios help?. (23rd August 2021) - Tan, Tracie HL; Perucca, Piero; Kwan, Patrick; O'Brien, Terence J; Monif, Mastura
Abstract : Objectives: Differentiating status epilepticus (SE) from prolonged episodes of psychogenic non-epileptic seizures (PNES) is not always straight forward and treatment paradigms are dichotomous with potential for harm from misdiagnosis. This study aims to identify the utility of the neutrophil-to-lymphocyte ratio (NLR), neutrophil-to-monocyte ratio (NMR), monocyte-to-lymphocyte ratio (MLR) and platelet-to-lymphocyte ratio (PLR) in differentiating between SE and PNES. Methods: Retrospective case control study in adults presenting to a tertiary hospital between April 2017 and December 2020. SE was defined as per ILAE criteria for time point 1. PNES events needed to meet the same time criterion. Patients were excluded if they had other factors that altered peripheral cell counts. After screening 1052 cases, 69 SE events from 56 patients and 38 prolonged PNES events from 22 patients were analysed. Results: NLR, NMR, MLR and PLR were all significantly higher in SE compared with PNES with mean values of 6.91 vs 2.09, 11.03 vs 7.94, 0.59 vs 0.27 and 189.7 vs 102.3, respectively. Using receiver operating curves, cut off values for NLR, NMR, MLR and PLR of >3.175, >9.36, >0.435 and >129.5 respectively were identified, yielding sensitivities and specificities of 60.87% and 89.47%, 53.62% and 78.95%, 56.5% and 94.7%, 59.42% and 86.84% respectively. AUC ranged from 0.689 to 0.7931. Conclusion: Patients with SE had significantly higher peripheral cell ratios than those with PNES. When the diagnosis is in doubt, elevated cell ratios can be used to increase diagnostic certainty. However, where cell ratios are not elevated, further investigations are required.